ANALISIS PEMETAAN SDM LOCAL DALAM PENGEMBANGAN KLASTER INDUSTRI GULA AREN BERBASIS KOMUNITAS - Iwan Manoppo; Reza Apreliah Dg Matara Matara; Elva Pobela; Adinda Yulianti (Fakultas Ekonomi dan Bisnis Universitas Islam DR KH EZ Mutaqien, 2026)
This study aims to analyze the potential and mapping of local human resources (HR) in the development of a community-based palm sugar industry cluster in Otam Village. The method used was Participatory Rural Appraisal (PRA) through participatory interviews, focus group discussions, and field observations. The collected data were then analyzed using a SWOT analysis. The results show that local HR in Otam Village has advantages in the form of traditional skills in sap tapping and palm sugar processing, as well as a culture of mutual cooperation that strengthens the community base. Weaknesses identified include limited business management, access to appropriate technology, and low marketing literacy. In terms of opportunities, the increasing demand for organic palm sugar in local and national markets opens up space for joint business development, while the main threats come from price fluctuations, competition with substitute products, and limited policy support. These findings confirm that the development of a palm sugar industry cluster in Otam Village requires a strategy to strengthen human resource capacity through technical training, business management, and digital-based marketing innovation. In addition, local institutional support and external partnerships are needed to strengthen the community's competitive position.